Multi-actor Synergy and Collaborative Governance in the SDGs-Based Management of MECoK Ecopark in Jepara: Sinergi Multiaktor dan Collaborative Governance dalam Pengelolaan MECoK Ecopark Berbasis SDGs di Jepara - Miladiya Cahyati; M. Nur Rofiq Addiansyah (Universitas Indo Global Mandiri, 2026)
Purpose : This study aims to analyze the synergy between multi-actor actors in the management of MECoK Ecopark in Jepara using the Ansell and Gash Collaborative Governance model perspective as a theoretical framework. Design/Methodology/Approach : The research adopted a qualitative approach using a case study. The study included primary data collected through interviews, documentation, and field observations. Secondary data was obtained through documentation studies on the organization's official website and literature review of e-books and e-journals. Findings : MECoK's management synergy aligns with Ansell and Gash's model of Starting Conditions, Facilitative Leadership, and Collaborative Process. However, there is a gap in Institutional Design, where collaboration is still conducted informally without a long-term management MoU. Nevertheless, MECoK has proven to contribute to the Sustainable Development Goals (SDGs). Practical Implications : Research suggests the need for accountability mechanisms, role redistribution, and more structured cooperation agreements to shift collaboration from dependence on specific actors to institutional sustainability. Originality/Value : Different from previous research that focused on socio-ecological aspects, this paper provides novelty by examining the synergy of MECoK management using a collaborative governance framework, while also contributing theoretically by demonstrating that cohesion between actors can substitute institutional formalization as a determinant of collaboration effectiveness. Paper Type : Case Study.